Monitoring the conformance of state structure plan outputs delivery using dynamic model - Muhammad Faris Abdullah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2013)
Plan outputs are the material objects that are tangible and provided as a result of the implementation of a development plan. They often act as precursor to achieving plan outcomes. Therefore, it is important to monitor the performance of plan in delivering its outputs so that the prospect of achieving its outcomes remains high. However, present state structure plan monitoring programmes focus mostly on monitoring land use change and not plan output delivery. The absence of output monitoring reduces the usefulness of the programmes and contributes to under-provision of outputs, especially public facilities and open spaces. This study proposes that state structure plan monitoring programmes must include mechanism to enable outputs delivery to be monitored. However, outputs requirement are dynamically linked to the number of population. Thus, any mechanism employed to monitor outputs delivery must be able to deal with this dynamic relationship between outputs and population. Hence, the aim of this study is to develop a dynamic model for monitoring state structure plan outputs delivery, and to analyse the model's ability in performing this task. To this end, a dynamic model for monitoring selected outputs is developed using STELLA software and applied on the Selangor State Structure Plan. The model consists of several non-spatial sub-models which are population, housing, schools and open spaces sub-models. The sub-models are linked to one another to reflect the dynamics of outputs requirement. Base year stock data and present stock data for the State of Selangor are keyed in into the model. The model also underwent several refinements in order to overcome the problem of unavailability of some data. The model is then used to run simulations to measure outputs conformity to plan's target and outputs gap to existing stock. The model simulation results show that the model can be used successfully to monitor the delivery of the selected outputs. At the same time, they also show that the Selangor State Structure Plan has performed poorly in delivering the selected outputs where outputs delivery has not conform to the plan's targets. The model simulations also show that these non-conformances will remain by the end of the plan's planning period. Nevertheless, the model's definition of non-conformance is rather rigid, with any deviation of outputs delivery from the plan's targets is considered as outright non-conformance. Future studies may look further in classifying the magnitude of the deviation into several degrees of conformity. Additionally, future studies may also look into the integration of the model with spatial based plan monitoring programmes, especially those that are GIS-based in nature.